Gambaran Kelengkapan Pengisian Resume Medis Di Rumah Sakit Umum Daerah Ende - Mekhtildis Suryati; Noor Yulia; Nanda Aula Rumana Aula Rumana; Deasy Rosmala Dewi (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2022)
ABSTRACTThe completeness of filling out a medical resume is very important to facilitate the main activities in the medical record unit and to support health services for patients who want to return for treatment after returning home. The medical resume must be filled in completely by the DPJP. This research was conducted in the medical record unit of the Ende Hospital from April to June 2021 with the aim of knowing the completeness of filling out a medical resume at the Ende Hospital. The method used is descriptive quantitative analysis method with data collection techniques, namely interviews, observations and literature studies. Based on the results of the study, from 81 samples of medical resumes, the average percentage of completeness of medical resumes was 92% and the average percentage of incompleteness was 8%. With details based on 4 components of quantitative analysis, the completeness of component 1 patient identification is 91% (74 RM), component 2 important notes is 87% (72 RM), component 3 author authentication is 95% (77 RM), and component 4 notes 98% (79 RM). Where the highest percentage of completeness is found in component 4 good notes of 98% (79 RM), and the most incomplete component is found in component 2 important notes of 13% (10 RM). This incompleteness resulted in the process of data management in the medical record unit being hampered and the quality of hospital services decreasing.Keywords : Completeness, Fill in Medical Resume ABSTRAKKelengkapan pengisian resume medis sangat penting untuk memudahkan kegiatan pokok di unit rekam medis dan menunjang pelayanan kesehatan bagi pasien yang mau berobat kembali setelah pulang rawat. Resume medis wajib diisi dengan lengkap oleh DPJP. Penelitianinidilakukan di unit rekam medis RSUD Ende bulan April sampai Juni 2021 dengan tujuan untuk mengetahui kelengkapan pengisian resume medis di RSUD Ende. Metode yang digunakan adalah metode deskskriptif analisis kuantitatif dengan teknik pengumpulan data yaitu wawancara, observasi dan studi pustaka. Berdasarkan hasil penelitian dari 81 sampel resume medis diperoleh rata-rata persentase kelengkapan pengisian resume medis sebesar 92% dan rata-rata persentase ketidak lengkapan sebesar 8%. Dengan rincian berdasarkan 4 komponen analisis kuantitatif, kelengkapan komponen 1 identifikasi pasien sebesar 91% (74 RM), komponen 2 catatan yang penting sebesar 87% (72 RM), komponen 3 autentifikasi penulis sebesar 95%(77 RM), dan komponen 4 catatan yang baik sebesar 98% (79 RM). Dimana persentase kelengkapan terbanyak terdapat pada komponen 4 catatan yang baik sebesar 98% (79 RM), dan komponen ketidaklengkapan terbanyak terdapat terdapat pada komponen 2 catatan yang penting sebesar 13% (10 RM). Ketidaklengkapan tersebut mengakibatkan proses pengelolaan data di unit rekam medis terhambat serta menurunnya mutu pelayanan rumah sakit.Kata Kunci : Kelengkapan, Isi Resume Medis